Potential Use of Open Source (Google Earth) Geospatial Data for Accurate Mapping - Case Study of UTP Campus - Obaidellah, Ahmad Taqiyuddin (2009)
This project titled `Potential Use of Open Source (Google Earth) Geospatial Data for Accurate Mapping - Case Study of UTP Campus' is basically a research on rectifying the UTP campus coordinate by taking references at the selected control points. The open source defined as the Google Earth Software and Geospatial Data is defined as the coordinates data. The study is based on the online mapping of the UTP campus map taken from the Google Earth. Locations of estimation at about 20 control points are decided to be the control point. These control points are randomly distributed in the UTP campus map. The control points selected should be the same control point in the Google Earth map and at the field area. For determining the coordinate from Google Earth map, a cursor is pointed at the each selected control points and the coordinate is taken for respective control points. For field work coordinate determination, the coordinates is taken by using the GPS instrument. This instrument is located at the same control points and the data reading process is done. The data collected using GPS instruments will be analyzed by using software namely as PCCDU and PINNACLE. A statistical study will be done between the survey coordinates with the Google Earth coordinates if there are differences in the coordinates comparison. These coordinates are transferred into the geosciences application software which is the ER Mapper and the ArcView GIS 3.2a for the rectification process. This project focuses on comparing the coordinates gained through the survey process with the coordinates released from Google Earth software. The data collection of this study has been collected, among the UTP campus at randomly distributed location of control points. There are 2 main objectives of this project that is to rectify coordinate of UTP campus and also to investigate the variance difference between the wrong coordinate with the actual coordinate. The aim of the project at the end of this research is to conclude whether the coordinates given by Google Earth are accurate to be use as reference coordinates.